Psychological Resilience And Its Relationship To The Completion Of The Push-Up (Ping Press) In The Iraqi National Paralympic Weightlifting Sport (Journal of the College of Basic Education, 2024)
The research aimed to identify the relationship between psychological resilience and the skill of pressure. The research hypothesized the existence of a relationship between psychological resilience and the skill investigated. It used the descriptive approach, the method of correlational relationships. The sample included 20 young lifters from Baghdad clubs, and it was concluded that the largest percentage of lifters are at a high level of psychological resilience. There is a significant correlation between psychological resilience and the skill of pressing pressure. It is necessary for psychological resilience to prevail among lifters because it has effective positive effects on the psychological state of players and reducing psychological pressures. Emphasis on the use of these objective measures by coaches because of its positive effects on the spirit. The morale and psychological state of the players.